Pengaruh Metode Neuro Muscular Taping (NMT) Terhadap Perubahan Peningkatan Fleksibilitas Fleksi Punggung Bawah - Emi Aprilyanti; Fransisca Xaveria Hargiani; Wahyu Teja Kusuma; Nurul Halimah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
The development of technology today not only has a positive impact on daily life but also has a negative impact on changes in individual habit patterns in activity including a decrease in active movement during activities and interacting that causes a decrease in the function of the body movement tool which if this is sustainable for a long time will affect the work of muscle structure, bones and joints and nerves so that there is the potential for a decrease in the function of the body's tools ranging from decreased flexibility, muscle imbalance and the emergence of Occupational Diseases (PAK). Neuro Muscular Taping (NMT) is a biomechanical technique that provides the capacity for functional enhancement of muscles and stimulation of the nervous system through the application of elastic adhesive tape. The purpose of this study is to find out the effect of NMT methods on changes in lower back flexion flexibility.